Relationship between Reflection and Decision-Making in Young People - Nataliia Shevchenko; Ivan Obyskalov (Insight: the psychological dimensions of society, 2025)
The purpose of the study is to determine the nature and significance of the correlation between reflection and decision-making in young people.  Methods. Empirical: the questionnaire “Style of Behavioral Self-Regulation” (Yevdokimova & Kobylko, 2023), the questionnaire “Ability to Self-Control” (Yevdokimova & Kobylko, 2023), D. Raven’s progressive matrices scale (Lemak & Petryshche, 2012), the test “Creativity” (Lemak & Petryshche, 2012), “Melbourne Decision-Making Questionnaire” (Petrovska, 2021), the methodology “Research of Volitional Organization of Personality” (Lemak & Petryshche, 2012); methods of statistical analysis: elucidation of the law of normal distribution, and Spearman’s correlation coefficient. Results. Psychological structures of reflection and decision-making are presented at three levels of their organization (the general level, the level of structural components, and the level of individual indicators). Several intermediate hypotheses about the presence and nature of the manifestation of the correlation between these processes were formulated and the corresponding indicators of strength and nature of the correlation at the level of organization of individual indicators and structural components at the general level were recorded. It has been established that a particular characteristic in the examination of highly integrated decision-making and reflection processes is the enhanced correlation observed as the synthetic level of the studied processes increases (progressing from specific indicators to general dimensions). Discussion and Conclusions. The assumption about a stable correlation between the processes of reflection and decision-making in young people at all levels of organization of the studied phenomena was confirmed. The level of the study of individual indicators revealed the ability “to describe the situation/event adequately and determine the main one and describe one’s thoughts and feelings” and the ability “to answer the search questions and be aware of the conditions of the situation in which this happens” have the highest level of the relationship with the decision-making process. The examination of the components of the researched processes revealed that thephases of experience review and reflective result possess a significant level of correlation with the cognitive and volitional domains of the individual involved in the decision-making process. The recorded results open the prospect of studies on the influence of reflection on the decision-making process in young people.